Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosome Repairs Endometrial Epithelial Cells Injury Induced by Hypoxia via Regulating miR-663a/CDKN2A Axis. (12th October 2022) - Wang, Hanbi; Liu, Simiao; Zhang, Wanyu; Liu, Meizhi; Deng, Chengyan
Abstract : Aim . Thin endometrium remains a severe clinical challenge with no effective therapy to date. We aimed at exploring the role and molecular mechanism of human umbilical cord mesenchymal stem cell- (hucMSC-) derived exosomes (hucMSC-Ex) in repairing hypoxic injury of endometrial epithelial cells (EECs). Methods . Exosomes were harvested from the conditioned medium of hucMSC and characterized using western blot, transmission electron microscopy (TEM), flow cytometry, and nanoparticle tracking analysis (NTA). EECs were subjected to hypoxic conditions before cocultured with hucMSC-Ex. Cell viability, apoptosis, and migration were determined with CCK-8, flow cytometry, and wound healing assay, respectively. Apoptosis/EMT-related proteins were detected by western blot. The miRNA profiling was determined by RNA sequencing. The expression of miR-663a and CDKN2A was measured by qRT-PCR. MiR-663a in EECs was overexpressed by transfecting with miR-663a mimics. Results . Mesenchymal stem cells (MSCs) markers CD73, CD90, and CD106 were positively expressed in hucMSCs. Exosome isolated from hucMSC expressed CD63 and TSG101, and were 100–150 nm in diameter. HucMSC-Ex promoted cell proliferation inhibited by hypoxia. And hucMSC-Ex also inhibited hypoxia-induced apoptosis, migration, and EMT of EECs by upregulating the expression of Bcl-2 and E-cadherin and downregulating Bax and N-cadherin levels. Further, bioinformatics research found that hucMSC-Ex coculture can significantly upregulate the expression of miR-663a and decrease the expression of CDKN2A in hypoxia-induced EECs. Furthermore, miR-663a overexpression inhibited CDKN2A expression and increased the expression of Bcl-2 and E-cadherin in hypoxia-induced EECs. Conclusions . HucMSC-Ex promoted cell proliferation, inhibited cell apoptosis, migration, and EMT in hypoxia-induced EECs, thereby alleviating hypoxia-induced EECs injury, which may be related to its regulation of miR-663a/CDKN2A expression. Our study indicated that hucMSC-Ex might benefit for repairing thin endometrium.